Evaluating the Validity of Acculturative Stress Scale on Afghan Refugee Adolescents in Iran - Baqir Rezai; Leila Heydarinasab; Rasol Roshan; Mohammad Gholami Fesharaki (Iranian Association of Health Education and Health Promotion, 2019)
Background and objective: More than half of Afghan refugees in Iran are adolescent. One of the important challenges in adapting to the new environment is the acculturative stress that can threaten the physical and mental health of refugee adolescents. In order to identify the acculturation stressors, the validity of the Acculturative Stress Scale on Afghan refugee adolescents in Iran was evaluated for the first time. Methods: The statistical population of the study is all Afghan refugee adolescent students in Iran who are studying at international schools in Tehran province. 406 participants were randomly selected, between the ages of 14 and 18, (166 boys and 240 girls). The tool of this research is an Acculturative Stress Scale that evaluates the translation validity, content validity and construct validity. Results: The results showed that the Acculturative Stress Scale in Afghan adolescent samples has good content validity. The results have confirmed the three factor structure of Acculturative Stress Scale in Afghan refugee adolescent samples in Iran. Exploratory factor analysis results for each variable was: process-oriented stress (32.76%), social stress (9.43%), and perceived discrimination (3.47%); this explained that in total 46% of the variance was explained by these three factors and the goodness index of fit is 0.40 which is at the very adequate level. Conclusion: This tool can be used to identify the risk factors in the adolescent refugee population. Also, this tool can examine the challenges of positive adaptation to the new environment and prevent mental disorders associated with acculturative stress. It is necessary for researchers to pay attention to the context, social and cultural status when assessing the acculturative stress.